Investigation of sociodemographic and substance use characteristics of cases referred to child and adolescent substance abuse treatment center - Kardaş, Ömer; Kardaş, Burcu (Journal of Dependence, 2023)
Objective: The aim of this study was to examine the sociodemographic, clinical and substance use characteristics of adolescents admitted to a child and adolescent substance abuse treatment center and to compare outpatients and inpatients in terms of these characteristics.Method: All files of the patients admitted to our center between 2018-2019 were retrospectively reviewed and analyzed. Results: The study included 197 patients (23 female, 174 male). The mean age was 16.3±1.1 years. School absenteeism was found in 73.6%, low academic achievement in 60.4%, disciplinary action in 67%, self-harm in 48.7%, forensic history in 52.8%, attention deficit hyperactivity disorder in 46.2%. Family history of substance use was 43.1%, family history of crime was 51.8%, and parental education level was low. The most common disorder was mixed substance use disorder (41%). The age of onset was as follows: cigarette (11.3), cannabis and volatile (13.7), exstasy and alcohol (14.4), heroin and synthetic cannabinoid (15). Family history of mental illness, coming home after 11 pm, opiate use disorder, heroin, methamphetamine, synthetic cannabinoid, volatile substance, cocaine and pregabalin use were higher in inpatients.Conclusion: Adolescents with substance use disorders were found to have more street life and delinquent behaviors and weaker ties with school. Adolescents with substance use disorders were found to have more street life and delinquent behaviors and weaker ties with school. Mixed substance use was frequent, with cannabis being the most commonly used substance. Inpatients were shown to have more unfavorable sociodemographic and clinical factors.
Keywords: Adolescence; addiction; substance use; addiction treatment center